Anthropological status of judokas of different skill level - Sertic, H.; Simunic, N. (4th European Science of Judo Symposium. Budapest, April 25th 2013, 2013)
Determination of anthropological status of judokas is crucial step in creating a specific training program for each sportsman. The level of abilities and knowledge`s is determination factor between judokas. MAIN GOAL of this research is to determine differences in anthropological status between judokas of different skill level. SAMPLE OF SUBJECTS included 43 judokas (U17). 23 judokas that compete on international level and 20 judokas that compete only on national level (in categories up to 55kg, up to 60kg and up to 66kg). SAMPLE OF VARIABLES: Forward bend (flexibility), Side steps (agility), Hand tap (hand speed endurance), Standing long jump (horizontal leg power), Static endurance in the position of "chin up" on judogi (arm and back static strength /endurance), Sit ups in 60 seconds (strength endurance of abdomen), Throw + 2 push-ups in 90 seconds (specific anaerobic endurance), Special judo fitness test (SJFT) (specific anaerobic endurance) . includes the number of throws for each series, heart rate immediately and one minute after the test and the overall test score. METHODS OF PROCESSING DATA: One way ANOVA was used to determine the difference between two groups of judokas. RESULTS showed generally statistically significant difference between the international and national level judokas (p = 0.0042). Univariate results for each variable showed that there were no differences in flexibility, agility, horizontal leg power, arm and back static strength /endurance and in heart rate immediately after the SJFT. Variables that differentiate judokas were hand speed endurance, strength endurance of abdomen, specific anaerobic endurance in both tests and the indicator of speed of recovery (heart rate one minute after the SJFT). One can CONCLUDE that the most reliable tests for differentiate judokas of are specific tests, and the ability that discriminate them the most is endurance.